Die Terrassen an der Seti Khola - Ein Beitrag zur quartären Morphogenese in Zentralnepal - Hormann, Klaus (ERDKUNDE, 1974)
The morphological contrast between the Himalayas and Subhimalayan Mountains is particularly pronounced in Central Nepal. Immediately south of the glaciated Annapurna, Himalchuli and Ganesh Himal ranges, the E-W-running Pokhara-Gurkha subsidence zone caused important qua ternary accumulations by all rivers coming from the Himalayas. In Eastern Nepal, such an accumulation zone in the northern parts of the Subhimalayan Mountains is missing. The terraced deposits of the Seti Khola river (Pokhara) served as the key for dating and classifying the quaternary deposits of Central Nepal. Near the Seti Khola, two types of younger quaternary deposits, the Pokhara gravels and the Gaunda conglomerate can be followed over 60 km and identified as deposits of two separated cold periods. Large scale tectonic movements in the time between the last two Himalayan glaciations ore responsible for the fact that north of Pokhara the (older) conglomerates form higher terrace levels than the Pokhara gravels, whereas in the whole Pokhara basin and up to 16 km downstream, the Gaunda conglomerate is covered by the Pokhara gravels. In the Pokhara basin, the terraces are mostly developed in Pokhara gravels, and terrace levels in general cannot be attributed to different accumulation sheets. In addition to the well preserved accumulation sheets of the last two Himalayan glaciations, older deposits probably of quaternary age have been studied. Central Nepal seems to present excellent conditions for the study of quaternary chronology in Asia. The photos (except no 6) give a profile following the Seti Khola river. Their regional sequence is: photo no 5 (northernmost), 4, 3, 1 and 2 (southernmost).